2023
DOI: 10.3390/inventions8050107
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Photovoltaic Modules Using Bio-Inspired Algorithms

Lucas Lima Provensi,
Renata Mariane de Souza,
Gabriel Henrique Grala
et al.

Abstract: This research aims to employ and qualify the bio-inspired algorithms: Particle Swarm Optimization (PSO), Genetic Algorithm (GA), and Differential Evolution Algorithm (DE) in the extraction of the parameters of the circuit equivalent to a photovoltaic module in the models of a diode and five parameters (1D5P) and two diodes and seven parameters (2D7P) in order to simulate the I-V characteristics curves for any irradiation and temperature scenarios. The peculiarity of this study stands in the exclusive use of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This phenomenon arises from the fact that the reference parameters are obtained from the technical sheet under STC conditions. The same characteristics can be observed in [15] where, according to the I-V curves were simulated in conditions far from the STC conditions, the accentuated error is visible by yourself. However, even choosing a more complex condition with G = 600 W/m 2 and Tc = 20 • C, the algorithms presented errors of less than 8%.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…This phenomenon arises from the fact that the reference parameters are obtained from the technical sheet under STC conditions. The same characteristics can be observed in [15] where, according to the I-V curves were simulated in conditions far from the STC conditions, the accentuated error is visible by yourself. However, even choosing a more complex condition with G = 600 W/m 2 and Tc = 20 • C, the algorithms presented errors of less than 8%.…”
Section: Resultssupporting
confidence: 68%
“…However, there are also models with greater complexity that are composed of a current source in parallel with two passive elements. These algorithms, despite being validated, tend to consume greater processing power and, in certain operating conditions, present greater errors [15]. Thus, the representation of energy generation from a photovoltaic module is carried out through simulations of photovoltaic electrical properties that are modeled by an electrical equivalence circuit [16].…”
Section: Introductionmentioning
confidence: 99%
“…Provensi et al, [27] address the challenge of evaluating photovoltaic module performance prior to deployment under different environmental conditions. The evaluation is done using photovoltaic modules provided in the manufacturer's data sheets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of a bioinspired models from a geometrical viewpoint is yet to receive sufficient research consideration. In addition, the use of bio-inspired approaches is recognized to be useful in different aspects associated with solar cells, and solar panels as seen in [26][27][28][29]. Furthermore, the focus of the considered research is shown in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The diode current I d in a PV system can be calculated using the diode equation, which describes the current-voltage characteristic of a diode. The diode current can be expressed as follows [40]:…”
Section: Pv System Plant Modeling 21 Pv Mathematical Modelmentioning
confidence: 99%